Poor and wealthy hand-to-mouth households in Belgium - Laurens Cherchye; Thomas Demuynck; Bram de Rock; Mariia Kovaleva; Geoffrey Minne; Maite de Sola Perea; Frederic Vermeulen (National Bank of Belgium, 2023)
We identify the population shares of poor hand-to-mouth households, wealthy hand-to-mouth households and non hand-to-mouth households in Belgium. We apply the methodology proposed by Kaplan and Violante (2014) and Kaplan, Violante and Weidner (2014) to the Belgian component of the Household Finance and Consumption Survey. We find that the fraction of hand-to-mouth households in Belgium is substantial and predominantly consists of wealthy hand-to-mouth households. We also compare the observable characteristics and marginal propensities to consume (MPCs) of the three household types We find that Belgian wealthy hand-to-mouth households have characteristics that resemble those of the non hand-to-mouth households, while their MPCs are often more similar to those of the poor hand-to-mouth households. This pleads for giving a unique place to each type of households when evaluating the effects of fiscal policy.
Keywords: D12; D15; E2; 330; savings; hand-to-mouth households; liquidity; marginal propensity to consume (MPC)